Autonomic Activity in Overweight-Obese Children During the Morning Transition in Cardiac Circadian Regulation (P21-065-19). (13th June 2019) - Pivik, R; Gu, Y; Downs, H; Andres, A; Jarratt, K; Bellando, J; Cleves, Mario
Abstract: Objectives: Regulation of the autonomic nervous system is disturbed in obese children and adults. This dysregulation—which includes sympathetic nervous system (SNS) over activity and disruption of cardiac circadian rhythms—is of interest because of the negative impact of these effects on cognition, regulation of energy homeostasis, cardiovascular health, and metabolic functions. The present study evaluated heart rate (HR) measures during the first hours following awakening from sleep when circadian cardiac control transitions from an emphasis on parasympathetic nervous system activity (PNS) during sleep to an emphasis on SNS activity during wakefulness. Methods: Resting HR recordings (5 min) were obtained from healthy normal weight (NW: BMI < 85 th %ile; n = 47; 25 boys) and overweight-obese (OB: BMI > 95 th %ile; n = 48; 24 boys) 10 yr olds enrolled in the ACNC's Brain Food study. The first of two recording sessions (T1) took place 2 hrs after awakening (1 hr after a standardized breakfast), and the second (T2) 1 hr later. Recordings were processed for measures of sympathetic [low frequency (LF)] and parasympathetic [high frequency (HF); vagal tone (VT); root mean square of intervals between adjacent heart beats (RMSSD)] activities. Results: Separate ANOVAs (recording session by group by sex) were conducted for each measure. Previous reports of higher HR in girls than boys and in OB than NW groups were confirmed (both P ≤ 0.001) HR slowed significantly from T1 to T2 for OB ( P = 0.021), but not NW. These effects were associated with T1 to T2 increases in SNS LF activity for both groups (both P ≤ 0.003), but significant increases in PNS measures (HF, RMSSD, VT; all P < 0.05) for only OB children. Increases in PNS activity across recording sessions for OB children attenuated group HR differences during T2 (T1: OB > NW, P = 0.008; T2: OB > NW, P = .051). Gender differences were consistent with faster HR in girls which was maintained across groups and recording sessions. Conclusions: The results are the first to show that autonomic dysregulation in obese children modulates the shift in SNS-PNS balance characteristic of the transition from sleep to waking. These findings may inform the development of new early intervention strategies to attenuate obesity that consider the role played by circadian rhythms. Funding Sources: Funded by USDA-ARS Project 6026-51000-010-05S.